Respostas
respondido por:
4
= 9 + [- 15 - (- 20 + 14) + (27)] - ( - 44 + 52)
= 9 +[-15 - (- 6) + 27] - (8)
= 9 + [ - 15 + 6 + 27] - 8
= 9 + [ - 15 + 33] - 8
= 9 + [18] - 8
= 27 - 8
= 19
= 9 +[-15 - (- 6) + 27] - (8)
= 9 + [ - 15 + 6 + 27] - 8
= 9 + [ - 15 + 33] - 8
= 9 + [18] - 8
= 27 - 8
= 19
deiamitna:
Tem que dar -35
respondido por:
1
9+[-15-(-20+14)+(27)]-(-44+52)
9 + [-15 - (-6) + 27] - (-44+52)
9 + [-15 + 6 + 27] - (-44 + 52)
9 + 18 -(8)
19
9 + [-15 - (-6) + 27] - (-44+52)
9 + [-15 + 6 + 27] - (-44 + 52)
9 + 18 -(8)
19
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás